2022
DOI: 10.1002/smll.202107354
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation‐Stimulated MSC‐Derived Small Extracellular Vesicle miR‐27b‐3p Regulates Macrophages by Targeting CSF‐1 to Promote Temporomandibular Joint Condylar Regeneration

Abstract: Small extracellular vesicles (sEVs) secreted by mesenchymal stem cells (MSCs) have been extensively studied in recent years. sEV contents change with the secreting cell state. When MSCs are exposed to an inflammatory environment, they release more functional growth factors, exosomes, and chemokines. Herein, MSCs are stimulated to alter sEV cargos and functions to regulate the inflammatory microenvironment and promote tissue regeneration. Sequencing of sEV miRNAs shows that certain RNAs conducive to cell functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 55 publications
3
19
0
Order By: Relevance
“…The culture medium was collected and centrifuged according to a previously reported protocol. 23 In brief, the medium was centrifuged at 300 g for 10 min to remove cells, 2000 g for 10 min to remove dead cells, 10 000 g for 30 min to remove cell debris, and 100 000 g for 70 min to remove contaminating proteins. The yielded pellet was washed in PBS at 100 000 g for 70 min to enrich the EVs and then resuspended in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The culture medium was collected and centrifuged according to a previously reported protocol. 23 In brief, the medium was centrifuged at 300 g for 10 min to remove cells, 2000 g for 10 min to remove dead cells, 10 000 g for 30 min to remove cell debris, and 100 000 g for 70 min to remove contaminating proteins. The yielded pellet was washed in PBS at 100 000 g for 70 min to enrich the EVs and then resuspended in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…After 14 days, the hydrogel was degraded by about 60% ( Figure 2 F). The membrane surface of EVs has g-acyl group and ε-amine group [ 30 ]. Therefore, TGase could enable EVs to be loaded onto the rhCol III hydrogel, thereby safely and effectively avoiding the sudden release of EVs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies demonstrated macrophages played diverse functions, including scavenging debris ( Peng et al, 2007 ; Wynn and Vannella, 2016 ), recruiting host cells ( Wang et al, 2018 ), promoting vascularization ( Sun et al, 2017 ), and inducing cell differentiation ( Wang et al, 2017 ). Most previous studies focused on the anti-inflammation ability of sEVs to polarize M1 macrophages to M2 macrophages ( Kwak et al, 2022 ; Li et al, 2022 ; Liu et al, 2022 ; Tang et al, 2022 ; Yang et al, 2022 ; Zhao et al, 2022 ). However, the role of macrophages in cell recruitment was largely unknown, especially in the process of tissue regeneration induced by sEVs.…”
Section: Discussionmentioning
confidence: 99%